The use of critical reflection manual in writing reflective journal: a case study of Malaysian student teachers’ perceptions - Wong, Yeou Min; Rosnidar Mansor,; Syakirah Samsudin, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Reflective journal writing is a common tool for reflection to engage student teachers (STs) in reflective practice during teacher clinical experience (TCE) or teaching practicum. However, studies have shown that STs who have undergone the TCE often demonstrated low levels of reflection in their reflective writings. Therefore, the purpose of this paper was to discuss the effectiveness of critical reflection manual (CRM) in promoting critical reflection among STs during TCE based on the STs’ perceptions. The CRM is developed through a systematic review of literature on various models of reflection, tools for reflection and approaches to developing a manual. It is developed specifically to guide STs to engage in critical reflection in their reflective writings during TCE. Primary data were collected from in-depth interviews and analysed by using content analysis technique. Eight STs from Sultan Idris Education University (UPSI) who were given exposure to the CRM during TCE were purposely selected to be interviewed. The findings indicated that the use of CRM by the STs had an overall positive impact. In addition, most STs gave positive perceptions of the CRM and provided several suggestions for improving the effectiveness of this CRM.